Programa Repromat y capacidad de resolucin de problemas en los estudiantes de Educacin Secundaria - Daz Ruz, Auber Pepe (2018)
This research work on the "REPROMAT" program and the ability to solve problems in the first grade students of Secondary Education of the I.E. "Republic of Panama" -Trujillo, 2017. Its fundamental purpose is to improve the ability to solve mathematical problems through the application of resources and / or educational materials, attractive as is the program "REPROMAT" to improve learning in the area of Mathematics and develop significant learning in students._x000D_ The research is applied, with quasi-experimental design with an experimental group and a control group with Pre and Post-Test. This research was conducted with a sample of 64 students, the 1st "A" formed by 32 students form the control group and the 1st "B" consisting of 32 students form the experimental group, both will be applied to the Pre and Post -Test, which yielded the following statistical results._x000D_ It was determined that the average difference of the pre-test is 0.03 points, which represents 0.03%; with value of the statistical test is tpre = 0.06 and level of significance greater than 5% (p> 0.05), showing that before applying the REPROMAT Program the students of the experimental and control group present a similar level in problem solving (homogeneous). It was also determined that the average difference of the post-test is 36.03 points, which represents 36.03%; The value of the statistical test is tpost = 8,359 and level of significance less than 5% (p <0.05), showing that after applying the REPROMAT Program, students in the experimental and control group present a significant difference in problem solving, where the experimental group improved the problem-solving capacity more than the control group; demonstrating the effectiveness of the REPROMAT Program in solving mathematical problems in the first grade students of Secondary Education of the I.E. "Republic of Panama" -Trujillo, 2017